Motion Event in Croatian, English, German and Italian Concerning Path Prefixes and Prepositions - Mikelić Preradović, Nives (Array, 2013)
We present an approach to encode translocative meaning and explore not only the possible, but also the preferred patterns for expressing this phenomenon in four languages: Croatian, English, German and Italian.We manually developed verb subcategorization frames for translocative meaning of prefixes PRE- and PRO-, enlarged the Croatian part of the bilingual dictionaries with the appropriate subcategorization frames and created the frame transition rules for three language pairs. The analysis presented here should indicate the possibilities of using obtained results for the development of both monolingual and bilingual verb dictionaries to facilitate foreign language acquisition, but also to improve the native language proficiency.